AN ASSESSMENT OF THE KNOWLEDGE, ATTITUDE AND BELIEF ABOUT HIV/AIDS AMONG STUDENTS IN TERTIARY INSTITUTIONS IN NIGERIA - Mohammed, A. I.; Babamba, B. Y. (Sokoto Educational Review, 2011)
H/V/AIDS among students in tertiary institution is an important consideration to psychologists and educators since the discovery of HIV/AIDS in Nigeria. However, in this study, the effort to assess student’s knowledge, attitude and belief is reported. The study was designed to assess these social variables of undergraduate student toward HIV/AIDS in Zaria. In order to effectively execute this study, six hypotheses, the sample size consisted of five hundred students who were drawn from three tertian’ institutions in Zaria. Statistical methods employed in analyzing the data were One-way analysis of variance (ANOVA), Pearson Product Moment Correlation Coefficient and t-test. The study revealed that no significant difference exists between male and female students, resident and non-residents as well as married and unmarried students in their knowledge, attitude and belief in HIV/AIDS. In addition, a significant difference exists between students in various academic levels and students from the three institutions understudied about their knowledge, attitude and belief toward HIV/AIDS. The study also shows that there is a relationship between students’ socioeconomic status and their knowledge, attitude and belief toward HIV/AIDS. It was recommended that students’ should take HIV/ADIS course and pass before graduating. This will give them sound information and equip them against the disease.